Characteristics and Trends of Radiology Research: A Survey of Original Articles Published in AJR and Radiology between 2001 and 2010 - Lim, Kyoung Ja; Yoon, Dae Young; Yun, Eun Joo; Seo, Young Lan; Baek, Sora; Gu, Dong Hyeon; Yoon, Soo Jeong; Han, Ari; Ku, You Jin; Kim, Sam Soo (Radiology, 2012)
To determine the characteristics and trends of the original articles published in two major American radiology journals, AJR American Journal of Roentgenology (AJR) and Radiology, between 2001 and 2010. This was a retrospective bibliometric analysis that did not involve human subjects and was exempt from institutional review board approval. All 6542 original articles published in AJR and Radiology between 2001 and 2010 were evaluated. The following information was abstracted from each article: radiologic subspecialty, radiologic technique used, type of research, sample size, study design, statistical analysis, study outcome, declared funding, number of authors, affiliation of the first author, and country of the first author. In addition, all the variables examined were presented along with the trend over time. The most common subspecialty of study was abdominal (1219 of 6542, 18.6%), followed by vascular/interventional (804 of 6542, 12.3%). A total of 3744 (57.2%) original articles used magnetic resonance (MR) imaging or computed tomography (CT), 5495 (84.1%) were clinical research articles, 3060 (46.8%) had sample size of more than 50, 4087 (62.5%) were retrospective, 4714 (72.1%) performed statistical analysis, 6225 (95.2%) showed positive study outcome, 4784 (73.1%) were not funded, 3942 (60.3%) had four to seven authors, and 5731 (87.6%) were written by the primary author who was from a department of radiology or radiology-related specialties. The United States published 45.5% (2975 of 6542) of the articles, followed by Japan (n = 525, 8.0%), Germany (n = 485, 7.4%), and South Korea (n = 455, 7.0%). In the time trend analysis, the following variables showed a significantly positive trend: cardiac subspecialty, CT and MR imaging as the radiologic techniques, type of research as other (nonbasic, nonclinical), sample size of more than 50, four to seven as the number of authors, medicine-related department of the first author, and South Korea and Italy as countries of the first author. On the other hand, pediatric subspecialty, combined (basic and clinical) type of research, and number of authors fewer than four showed a significantly negative trend. The bibliometric analysis of the AJR and Radiology journals with articles published between 2001 and 2010 revealed characteristics and trends of the current radiology research that may provide useful information to researchers and editorial staff in radiology.